Depletion of growth differentiation factor 15 (GDF15) leads to mitochondrial dysfunction and premature senescence in human dermal fibroblasts. Issue 1 (22nd December 2022) - Wedel, Sophia; Martic, Ines; Guerrero Navarro, Lena; Ploner, Christian; Pierer, Gerhard; Jansen‐Dürr, Pidder; Cavinato, Maria
Abstract: Growth differentiation factor 15 (GDF15) is a stress‐responsive cytokine also known as a mitokine; however, its role in mitochondrial homeostasis and cellular senescence remained elusive. We show here that knocking down GDF15 expression in human dermal fibroblasts induced mitochondrial dysfunction and premature senescence, associated with a distinct senescence‐associated secretory phenotype. Fibroblast‐specific loss of GDF15 expression in a model of 3D reconstructed human skin induced epidermal thinning, a hallmark of skin aging. Our results suggest GDF15 to play a so far undisclosed role in mitochondrial homeostasis to delay both the onset of cellular senescence and the appearance of age‐related changes in a 3D human skin model. Abstract : Depletion of growth differentiation factor 15 (GDF15) leads to mitochondrial dysfunction and premature senescence in human dermal fibroblasts. GDF15, a mitokine regulated in response to different sources of stress, is upregulated during cellular senescence and in the plasma of aged animals, including humans. In normal cells, under stress conditions, transcription and secretion of GDF15 are increased, although the mechanisms of intra and extracellular action of this protein are still not fully understood. Here, we demonstrate that knockdown of GDF15 induces premature senescence in human dermal fibroblasts. In this context, senescence was characterized by the accumulation of ROS, mitochondrial dysfunction, and secretion of a distinct SASP. When inserted in 3D skin equivalents, senescent GDF15 knockdown fibroblasts induced epidermal thinning, a common characteristic of skin aging, supporting the important role of GDF15 in maintenance of cell homeostasis.